1994
DOI: 10.1037/0735-7028.25.3.288
|View full text |Cite
|
Sign up to set email alerts
|

Effects of patient age on neuropsychological test interpretation.

Abstract: Normative test data for a 38-year-old and for a 74-year-old were obtained for the Halstead-Reitan Neuropsychological Battery, the Wechsler Adult Intelligence Scale-Revised, and the Wechsler Memory Scale. These test protocols were presented for blind interpretation to a random sample of psychologists specializing in neuropsychology. Test results for the "average" elderly person were interpreted as normal less frequently (42%) than results for the "average" younger adult (93%). The elderly person's test results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…Research has demonstrated that individuals working under conditions of uncertainty tend to overestimate the probability that their judgments are correct, and it appears that mental health professionals are as susceptible to overconfidence as non-professionals (Faust, Hart, Guilmette, & Arkes, 1988;Nadler, Mittenburg, DePiano, & Schneider, 1994;Rabinowitz & Garelik-Wyler, 1999). However, we know little about the sources of this overconfidence.…”
Section: Introductionmentioning
confidence: 88%
“…Research has demonstrated that individuals working under conditions of uncertainty tend to overestimate the probability that their judgments are correct, and it appears that mental health professionals are as susceptible to overconfidence as non-professionals (Faust, Hart, Guilmette, & Arkes, 1988;Nadler, Mittenburg, DePiano, & Schneider, 1994;Rabinowitz & Garelik-Wyler, 1999). However, we know little about the sources of this overconfidence.…”
Section: Introductionmentioning
confidence: 88%
“…Deception was practised: although the neuropsychologists were told that the results were obtained for a 38-year-old client and a 74-year-old client, they were actually given average scores for relatively normal 38-year-old and 74-year-old individuals residing in the community (these values were based on normative data). With regard to results, in the study by Nadler et al (1994), diagnoses of dementia were never made for the 38-year-old client, but 23% of the neuropsychologists made this diagnosis for the 74-year-old client. This result is remarkable because the client was described using the test results for 74-year-old individuals in the community with no known neurological disorder.…”
Section: Clinical Judgment and Validitymentioning
confidence: 95%
“…Evidence for age bias has been mixed (Garb & Boyle, in press;Nadler, Mittenberg, DePiano, & Schneider, 1994). In both studies, neuropsychologists made diagnoses for a 38-year-old client and a 74-year-old client.…”
Section: Clinical Judgment and Validitymentioning
confidence: 99%
“…Specifically, the performance on neuropsychological assessment in normal elderly people with very low educational attainment is significantly lower with greater variability than those with more educational attainment 23. This puts elderly people with low education at higher risk for misdiagnosis with pathological aging in the clinical setting, including mild cognitive impairment 456. Estimating premorbid cognitive functioning with an appropriate measure is crucial for accurate diagnosis and thereby, would contribute to effective prevention and treatment of neurocognitive disorders in these individuals.…”
Section: Introductionmentioning
confidence: 99%